SUMO Wrestles with Recombination - Altmannová, Veronika; Kolesár, Peter; Krejčí, Lumír (Biomolecules, 2012)
DNA double-strand breaks (DSBs) comprise one of the most toxic DNA lesions, as the failure to repair a single DSB has detrimental consequences on the cell. Homologous recombination (HR) constitutes an error-free repair pathway for the repair of DSBs. On the other hand, when uncontrolled, HR can lead to genome rearrangements and needs to be tightly regulated. In recent years, several proteins involved in different steps of HR have been shown to undergo modification by small ubiquitin-like modifier (SUMO) peptide and it has been suggested that deficient sumoylation impairs the progression of HR. This review addresses specific effects of sumoylation on the properties of various HR proteins and describes its importance for the homeostasis of DNA repetitive sequences. The article further illustrates the role of sumoylation in meiotic recombination and the interplay between SUMO and other post-translational modifications.